Hepatic microcirculatory thrombosis in acute-on-chronic hepatic failure - Ehab F Mostafa; Waleed A Ismael; Amr El Hawary; Ayman Marei; Sameh Saber (SpringerOpen, 2018)
Background Acute-on-chronic hepatic failure is an increasing number of identified distinct disorders encompassing an acute deterioration of hepatic functions in patients with chronic liver disease Aim The aim was to evaluate the possibility of hepatic microcirculatory thrombosis in acute-on-chronic hepatic failure and the value of plasma fibrin monomer (FM) and D-dimer in the diagnosis. Patients and methods A total of 50 patients with chronic hepatitis C infection developing new-onset ascites, encephalopathy, and/or jaundice with raised international normalisation ratio (INR) (group 1); group 2 included 30 patients with compensated chronic hepatitis C virus infection who served as the control group. Ascetic fluid examination and culture were done for group 1, in addition to complete blood count, liver enzymes, INR, serum bilirubin and albumin, blood culture, α-fetoprotein, D-dimer, plasma FM, abdominal ultrasound, and Doppler for portal vein were done for all patients groups. Results Group 1was subdivided according to the level of FM into subgroups A and B. FM showed a significant difference between group 1A and other groups; group IB showed nonsignificant elevation of the level of FM and a significant increase in D-dimer compared with the control group. A marked reduction in portal flow mean velocity in group 1A was recorded with further deterioration of portal flow direction after 2 weeks from the admission time. Three months follow-up showed significant reduction of FM, improvement of portal flow mean velocity and direction in group 1A; FM was significantly positively correlated with portal flow mean velocity. Conclusion Hepatic microcirculatory thrombosis may occur in acute-on-chronic hepatic disease; determination of the FM and D-dimer level may be useful biomarkers predicting hepatic microcirculatory thrombosis.